"Global" Sovereignty. The Latin American Case [Soberanía "globalizada". El caso latinoamericano] - Chininín, M. (2017)
This article refers to the importance that sovereignty, as substantial element of constitutional law and integration law has in the process of globalization. It is explained that the rise and development that currently it has, is concomitant to the loss of sovereignty by the traditional state. The loss of sovereignty by the state against globalization is the result of the boom that now has community law, derived of mismanagement that has existed by the states in the administration of their right to selfdetermination.